2008
DOI: 10.1179/136485908x278793
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidiumspecies causing acute diarrhoea in children in Antananarivo, Madagascar

Abstract: A 13-month study of children presenting with acute diarrhoeal disease at hospitals and rehydration clinics in Antananarivo, Madagascar, was undertaken between May 2004 and May 2005. Cryptosporidiosis accounted for diarrhoea in 12 (5.6%) of the 215 children investigated. Cases of cryptosporidiosis were detected only in the rainy season, and the median age of cases was 13.5 months (range=1 day-27 months). As 11 of the cases of cryptosporidiosis were caused by Cryptosporidium hominis and only one by C. parvum, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…G. lamblia showed the significant high risk age group as >5-14 yrs, though the lesser age groups were also involved. The detection rate of Cryptosporidium spp is comparable with other investigations [16,26]. Two major observations recorded in this study were the infection of Giardia in the adult patient group of up to 20 years and significant association of Giardia as co-infection with other pathogens.…”
Section: Discussionsupporting
confidence: 90%
“…G. lamblia showed the significant high risk age group as >5-14 yrs, though the lesser age groups were also involved. The detection rate of Cryptosporidium spp is comparable with other investigations [16,26]. Two major observations recorded in this study were the infection of Giardia in the adult patient group of up to 20 years and significant association of Giardia as co-infection with other pathogens.…”
Section: Discussionsupporting
confidence: 90%
“…In fact, the results of several other subgenotyping studies, from other areas of the world, have also indicated a similarly large degree of heterogeneity, in a restricted geographical location, to that described here. In Madagascar, for example, three subtype families (Ia, Id and Ie) were recently identified amongst just eight C. hominis isolates from children (Areeshi et al, 2008). Furthermore, Gatei et al (2008) suggested that, in developing countries (as seen in studies in India, Malawi and Peru), subtype heterogeneity is common, and only in industrialized countries (as seen in studies from the U.K. and Portugal) is subtype homogeneity more usual.…”
Section: Discussionmentioning
confidence: 99%
“…The environmentally resistant oocysts are fully sporulated when they are excreted in feces, and therefore they are immediately infectious (116,441,477). Infections are usually characterized by self-limiting diarrhea associated with severe abdominal pain in both immunosuppressed and immunocompetent persons, especially HIV-infected persons and children worldwide (16,116,390). The duration of clinical symptoms is highly dependent on the person's immunological competence (235).…”
Section: Cryptosporidium Speciesmentioning
confidence: 99%